Implementation of Problem-Based Learning Model to Improve High School Students' Problem-Solving Ability on Physics Materials - R, Aisya; Usman, Usman; Khaeruddin, Khaeruddin; Setiawan, Trisno (Department of Physics Education, Universitas Mataram, 2024)
This research aims to see whether there is an influence of the problem-based learning model on students' problem-solving abilities in physics material at SMAN 9 Gowa. This research is Pre-Experimental research using One Group Pretest-Posttest Design so that only one class without control class. The population of this study were students of class XI MIPA 1 until XI MIPA 5. The research sample was taken using a simple random class technique, namely class XI MIPA 5 SMAN 9 Gowa. The research instrument is a test instrument for students' physics problem solving abilities in the form of 6 selected essays that use the valid criteria. The research results showed that the physics solving abilities of class XI MIPA 5 students before being taught by applying the problem based learning model were in the low problem category as indicated by the average score of 42.5. Problem solving ability of students before the application of the PBL model is 64% in the medium category, 32% in the low category and 4% in the very low category. The ability to solve physics problems of class XI MIPA 5 students after being taught by applying the problem based learning model is in the high category as shown by the average score of 61.7. Problem solving ability of students after applying the PBL model is 56% in the high category, and 44% in the medium category and nothing student have low and very low problem solving ability. In the pretest, problem solving ability has the lowest score is 19, the highest score is 47 and the average score is 42.5 which is in the medium category with a standard deviation is 6.7, while in the posttest, the lowest score is 50, the highest score is 75, and the average score is 61.7 which is in the high category with a standard deviation is 6.8. There was a significant increase in the physics problem solving abilities of class XI MIPA 5 students after being taught using the problem-based learning model with the N-Gain category = 0.34 (medium criteria).